Accessing customer's behaviour towards online hotel reservation / Nurzaimah Ismail and Nur Hazwani Sulaiman - Ismail, Nurzaimah; Sulaiman, Nur Hazwani (Faculty of Hotel and Tourism, Universiti Teknologi MARA, 2018)
Online purchasing nowadays is an essential instrument for hotels to reach and connect with guests, gain strong guest loyalty, and encourage repeat patronage. In the present hotel industry, shift and trend from online purchasing has give a positive impact for hotel operators to gain exclusive purchasing from their guests. By examining the fundamental factors that influence customers' attitude and purchase behaviour toward online hotel room reservations which include information, trust price and convenience, major 5-star hotels will be assessed in accordance to the four factors framework. Thus, the study aimed to examine the factors that influence customers' attitude and purchase behaviour toward online hotel room reservations. This study offers better understanding of the factors that influencing customers’ attitude and purchasing behaviour toward online hotel room reservations.